Parenting Management in Strengthening Children's Religious Character Education - Tamjidnor, Tamjidnor (JURNAL AL-TANZIM, 2022)
Globalization allows foreign cultures to quickly enter and often hurts children's behavior, especially teenagers classified as unstable. If this is not balanced with a qualified religious character, teenagers can experience a moral decline. This study seeks to examine the strengthening of religious character education in children in madrasas with parenting management to regulate and control the habituation of children at home so that excellent and religious characters are formed. This research uses a descriptive qualitative approach with a case study type. The research locations are Madrasah Tsanawiyah throughout the city of Banjarmasin. The data analysis technique used is the Miles and Huberman technique in data reduction, data display, and data verification or conclusions. The results showed that Madrasah Tsanawiyah institutions throughout the city of Banjarmasin strengthen planning that coordinates with parents of students; second, religious character management is carried out using religious habituation, time management, and follow-up progress. The implications of strengthening religious character education in coordination with parents can instill religious character in children by habituation.